Peningkatkan QoS Layanan Video Call dengan Metode DASTFBC Sistem MIMO2x2 pada Jaringan LTE - Irmayani Irmayani (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
ABSTRACT The DASTFBC (Diagonal Algebraic Space Time Frequency Block Code) method is a coding scheme that utilizes different diversity sources, namely space, time and frequency. This method is one method that can be used to improve video call services. The DASTFBC method uses a rotation matrix in the DAST code which is formed using algebraic number field theory. The code matrix structure consists of rotated information symbols, expanded using a square diagonal code matrix. This method is used to overcome signal power fluctuations at the receiver which cause the service quality to decrease (not comply with) BER video call standards. The DASTFBC method is applied to the LTE network MIMO system with 64 QAM modulation. This method will be simulated in the Matlab program to obtain results to improve video call services. The DASTFBC method simulation of BER was carried out for 4 user speed scenarios, namely 5km/hour, 40km/hour, 100km/hour, 120km/hour. Significant results of the DASTFBC method can already be seen when the user moves at 40km/ hour. With this method, a smaller BER value is obtained, namely 2x10-4, this shows that with the DASTFBC method the video call BER standard (10-3) can be met. The value of BER obtained when using DASTFBC with a speed of 120km/h is 8.5x10-3 this value almost exceeds the standard BER video call. So that the maximum speed of the user when using the DASTFBC method is 120km/h above that speed the standard value of the BER video call cannot be fulfilled. Keywords: video call, LTE network, MIMO, DASTFBC